Le vie chirurgiche conservative: anca - Brioschi, M.; Favilla, S.; Pace, F.; Giai Via, A.; Randelli, F. (Lo Scalpello - Journal, 2018)
CONSERVATIVE SURGICAL APPROACHES: THE HIPThe most common conservative approaches to the hip joint are the anterior, the Ganz safe surgical dislocation and themedial approach. The anatomy of these approaches is described in detail in this review. Each approach is alsoevaluated considering the surgical conservative indications, technique, and complications.